Foreign Entry in Turkey's Banking Sector, 1980-97 - Denizer, Cevdet (World Bank, Washington, DC, 2015)
Despite high and volatile inflation, a record number of foreign and local banks entered Turkey's banking sector after the country relaxed rules about bank entry, and generally eliminated controls on interest rates, and financial intermediation in 1980. The country's financial integration with the rest of the world took a big step forward with the opening up of the capital account in 1989. Capital inflows rose significantly, and the financial system became increasingly linked with external markets. The author examines one dimension of liberalization: the impact of foreign banks entering the financial sector. Between 1980 and the end of 1997, 17 foreign banks, and a number of new local banks entered the sector. The author investigates how these banks' entry into the sector affected performance, based on three measures: net interest margin, overhead expenses, and return on assets (all expressed as a percentage of total assets). He finds that: 1) Foreign bank ownership is related to all three performance measures. 2) Foreign bank entry reduced the overhead expenses of domestic commercial banks, strengthening profits. 3) Despite their small scale operations, foreign banks entering the sector had a strong effect on competition. But the market could use more competition. 4) There are strong indications that foreign banks had a positive impact on financial, and operational planning, credit analysis and marketing, and human capital.